PENGATURAN PEMUTUSAN HUBUNGAN KERJA (PHK) KAITANNYA DENGAN IKLIM INVESTASI DI INDONESIA - Anggun Kirana; Annisaul Maslamah; Devi Riyani; Lidia Fathaniyah; Istiqomah Putri W (JURNAL AKTA YUDISIA, 2023)
AbstractThis research will examine whether rigid termination of employment arrangements affect the investment climate in Indonesia. This research is a normative legal research using a statutory approach. The primary legal materials used are Law Number 6 of 2023 and secondary legal materials, namely books, journals, and the results of other people's research related to the problem. the results of the study found that the regulation of layoffs Number 6 of 2023 cannot be viewed partially from one side only. From the entrepreneur's point of view, the most flexible layoff arrangements can encourage employers' activities to continue to adapt to the market. However, from the workers' point of view, with the flexibility of layoff arrangements, this actually poses a threat of unilateral layoffs, which is not impossible to cause new problems for the country, such as increasing unemployment and poverty. Keywords: Pemutusan Hubungan Kerja, Iklim Investasi, UU Cipta Kerja